The association of pre-operative home accelerometry with cardiopulmonary exercise variables - Cui, H; Kirby, G; Surmacz, K; Hargrove, C; Griffiths, J; Turney, B (Wiley, 2017)
We investigated the association of pre-operative activity, reported by the Duke Activity Score Index, Short Form-12 and measured by an accelerometer worn at home, with five cardiopulmonary exercise variables: peak power; peak oxygen consumption; anaerobic threshold; and ventilatory equivalents for oxygen and carbon dioxide. Fifty patients scheduled for major surgery underwent a standard pre-operative cardiopulmonary exercise test and wore a chest-mounted triaxial accelerometer for a mean (SD) duration of 3.2 (0.4) days. The Duke Activity Score Index and six accelerometer variables were significantly correlated with all five cardiopulmonary exercise variables, Pearson correlation coefficients 0.5 to 0.7, p = 0.02 to p < 0.001. Our results can guide future studies that measure physical activity for pre-operative assessment and interventions.